Comparison of PID and EPID controllers in self balancing robot - AKPOLAT, ALPER NABİ (My University, 2023)
Two wheeled Self balancing robots have become more popular in recent times and used in many applications, commonly used in transportation as these balancing robots are faster and apparently stable. Balancing is achieved by using controllers tuned for the system. Inverted pendulum principle is used in these robots. This paper proposes the use of two control methods, namely Proportional-Integral-Derivative (PID) and Extended PID (EPID), for maintaining the balance of two-wheeled and self-balancing robots, even when slightly tilted, thus preventing them from falling. PID control theory generally depends up on transfer functions, this paper extends the theory using EPID. EPID provides a new perspective on the working principle of PID control and its relationship with other control theories, such as tracking control and disturbance observer. This approach is illustrated using the fundamental principle of inverted pendulum technology. The key advantage of these robots over other mobile robots is their increased stability due to zero turning radius, which allows for smoother rotations during changes in direction.
Keywords: Tıp; Sosyal ve Beşeri Bilimler; Sosyoloji; Kütüphanecilik; Bilgi Sistemleri, Haberleşme ve Kontrol Mühendisliği; Sinyal İşleme; Bilgisayar Bilimleri; Algoritmalar; Bilgi Güvenliği ve Güvenilirliği; Sağlık Bilimleri; Temel Tıp Bilimleri; Biyoistatistik ve Tıp Bilişimi; Mühendislik ve Teknoloji; Medicine; Social Sciences and Humanities; Sociology; Library Sciences; Information Systems, Communication and Control Engineering; Signal Processing; Computer Sciences; algorithms; Information Security and Reliability; Health Sciences; Fundamental Medical Sciences; Biostatistics and Medical Informatics; Engineering and Technology; Klinik Tıp (MED); Mühendislik, Bilişim ve Teknoloji (ENG); Sosyal Bilimler (SOC); Klinik Tıp; Bilgisayar Bilimi; Mühendislik; Sosyal Bilimler Genel; TIBBİ BİLİŞİM; BİLGİSAYAR BİLİMİ, YAPAY ZEKA; BİLGİSAYAR BİLİMİ, BİLGİ SİSTEMLERİ; TELEKOMÜNİKASYON; MÜHENDİSLİK, ELEKTRİK VE ELEKTRONİK; BİLGİ BİLİMİ VE KÜTÜPHANE BİLİMİ; Clinical Medicine (MED); Engineering, Computing & Technology (ENG); Social Sciences (SOC); CLINICAL MEDICINE; COMPUTER SCIENCE; ENGINEERING; SOCIAL SCIENCES, GENERAL; MEDICAL INFORMATICS; COMPUTER SCIENCE, ARTIFICIAL INTELLIGENCE; COMPUTER SCIENCE, INFORMATION SYSTEMS; TELECOMMUNICATIONS; ENGINEERING, ELECTRICAL & ELECTRONIC; INFORMATION SCIENCE & LIBRARY SCIENCE; Bilgisayar Ağları ve İletişim; Fizik Bilimleri; Bilgisayar Bilimi Uygulamaları; Bilgisayarla Görme ve Örüntü Tanıma; Bilgi sistemi; Bilgi Sistemleri ve Yönetimi; Sosyal Bilimler ve Beşeri Bilimler; Elektrik ve Elektronik Mühendisliği; Tıbbi Bilişim; Computer Networks and Communications; Physical Sciences; Computer Science Applications; Computer Vision and Pattern Recognition; Information Systems; Information Systems and Management; Social Sciences & Humanities; Electrical and Electronic Engineering; Health Informatics; Enhanced Proportional Integral Derivative controller; Inverted pendulum; Proportional - Integral - Derivative controller; Self-balancing robot